European standards of higher education quality assurance: peculiarities and perspectives of introduction in Ukraine - Kotsan, Ihor; Liakisheva, Anna; Коцан, І.; Лякішева, А. (Східноєвропейський національний університет імені Лесі Українки, 2017)
European standard of higher education is rather a new phenomenon. Each meeting of the Ministers of Education of the participating countries of the Bologna Process touched the ways of solving common problems of higher education quality. In fact, already in the first unifying documents that developed strategic perspectives of Europe of Knowledge, it was specified the ways of quality assurance of higher education. Quality education is high quality education that enables providing of successful vital activity of the society. A personality acquires education, and its quality directly affects progressive transformations of the society. That is why the government, taking care of the highest quality of education for its citizens, indirectly affects its own economic and social progress. Before the emergence of common European interests on ensuring the quality of higher education, in each country it was formed their own approaches to understanding of this phenomenon.
Keywords: еuropean standards; higher education; higher education quality assurance